Fine-grain heat affected zone softening of G115/Sanicro25 dissimilar steel welded joints after post-weld heat treatment. (December 2020) - Yang, Maohong; Zhang, Zheng; Liu, Yanrong; Li, Linping; Huang, Jiankang
Abstract: The mechanical properties of the G115/Sanicro25 dissimilar steel welded joints were characterized by room temperature tensile and microhardness. The microstructures of fine-grain heat affected zone (FGHAZ) and base metal (BM) in the G115 steel side were characterized by optical microscopy, SEM, TEM, and XRD. The results show that as the strain increases, weld beam first yields and hardens, the stress on the specimen is further increased, then Sanicro25 steel yields and hardens, and G115 steel yields finally, the specimen broken in the FGHAZ of G115 steel side. The FGHAZ of G115 steel side softens after post-weld heat treatment (PWHT). The size of the heat-affected zone (HAZ) on the G115 side after welding is 3.7 mm. After PWHT, dynamic recovery occurs in the FGHAZ of the G115 side. The precipitates increase, martensite laths are polygonal, dislocation density is reduced, residual austenite disappears. The FGHAZ with large residual stress after welding undergoes stress relaxation during PWHT. Residual stress in the FGHAZ is reduced, the dislocation density is reduced, which reduces the effect of dislocation strengthening and martensite lath strengthening. The strength of the FGHAZ is lowered than BM. Highlights: The deformation of the joint is uneven. After PWHT, dynamic recovery occurred in the FGHAZ, dislocation density reduced. Decreased dislocation strengthening effect is the main cause of fracture.